Estimation of residual operability and energy efficiency optimization of oil purification column - Marko S. Jaric; Sanja Z. Petronic; Ivana V. Vasovic Maksimovic; Nedzad R. Rudonja; Martina M. Balac; Marko D. Ristic (Case Studies in Thermal Engineering)
This paper examines the process of oil distillation in upstream oil and gas facilities, along with the main equipment involved. A vertical column, a key component of the stabilization system that has been in operation for almost 20 years, was tested. The column was temporarily taken out of service to conduct a detailed, non-destructive inspection. Due to its long-term operation, aging, and exposure to corrosive environments—especially oil corrosion—it represents high-risk equipment with potential environmental and financial consequences in the event of failure. This study aims to determine the optimal operating mode to improve output product quality. Ultrasonic thickness testing (UTT) was performed, revealing wall thinning in critical areas. The maximum calculated corrosion rate was 0.0722 mm/year, and the remaining service life was estimated at 26 years. Based on the risk-based inspection (RBI) analysis, the column falls into the high-risk category, emphasizing the importance of optimized inspection planning. An RBI analysis was conducted using API 581 methodology, classifying the column as high-risk equipment with potential financial consequences exceeding €2.7 million per year. In parallel, four different operating regimes were tested to optimize energy utilization and product quality. The optimal regime achieved a heat transfer of 100.07 MW, minimal CO2 and H2O concentrations, and maximum recovery of C3–C5 hydrocarbons. This paper highlights the importance of condition monitoring, targeted inspection strategies, and energy optimization in extending equipment life and reducing operational risks. This approach enhances reliability and cost-effectiveness in oil and gas facilities while prioritizing environmental protection.